Liability of pharmacists in Malaysia / Intan Sharina Nasri, Azimah Nor Idris and Dg. Roslina Datu Mohamad. - Nasri, Intan Sharina; Nor Idris, Azimah; Datu Mohamad, Dg. Roslina (Faculty of Law, 2006)
Study on the liability of pharmacists in Malaysia according to the statistic in 2004, there are 4613 registered pharmacists. Problem arise is that pharmacists are now selling medication without prescription and the offences are increasing from years to years. This project paper will be looking at the various legislations to pharmacists such as Poison Act 1952, Registration of Pharmacists Act 1951, Dangerous Drugs Act 1952, Sales of Drugs Act 1952, Control of Drugs and Cosmetics Regulation 1984 and etc. this act is used because to looks at the regulations relating to duties, liabilities and offences if they breach their duties. However, all this Acts regulated since the year of 1951. Therefore, the amendment with regard to certain provisions needs to be made to fit it with the recent situation. The certain sections should be repeal such as to increase the amount of penalties, to conduct a training to improve and exposed them with the information, knowledge and skills needed. There are some provision must be add in relating to their Code of Conduct in the Act.